Parallel Diplomacy of the City of Solo for Regional Culture Preservation through Solo International Performing Arts (SIPA) - Khairunnisa, Ayuningtyas; Azmi, Fuad (Dinasti Research, 2025)
This study analyzes the parallel diplomacy practices of Solo City in preserving regional culture through the implementation of Solo International Performing Arts (SIPA) for the 2021-2025 period. The main issues examined are the suboptimal parallel diplomacy framework, declining interest of the younger generation in traditional arts, and minimal follow-up on international cooperation after the event. The research uses a descriptive qualitative method with data collection techniques through semi-structured interviews with the Director of SIPA and officials from the Solo City Tourism, Youth, and Sports Agency, direct observation at SIPA 2025, and a study of official documents from the Ministry of Tourism and Creative Economy and the Solo City Government. The results of the study show that the Solo City Government acts as an autonomous initiator, facilitator, and coordinator in SIPA without explicit direction from the central government, fulfilling the characteristics of parallel diplomacy through subnational initiatives, cross-actor involvement, and an orientation towards preserving the local identity of